2015
DOI: 10.1177/0268355514568848
|View full text |Cite
|
Sign up to set email alerts
|

Conservative versus surgical treatment of venous leg ulcers: 10-year follow up of a randomized, multicenter trial

Abstract: The addition of surgical treatment in patients with venous ulceration leads to a significantly higher chance of being ulcer-free, than just ambulatory compression therapy. This effect persists after 10 years of follow up. The number of incompetent perforating veins has a significant effect on the ulcer-state and recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 14 publications
(14 reference statements)
1
32
0
1
Order By: Relevance
“…At the time of publication of the systematic review7, the ESCHAR RCT21 reported substantially fewer recurrences after surgery at 4 years, whereas van Gent and co‐workers31 showed no difference in recurrence at 2 years. However, recently published long‐term follow‐up from the latter study showed that surgery almost halved the probability of recurrence at 10 years32, corroborating the outcome of the ESCHAR trial21. Nevertheless, these data should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 54%
“…At the time of publication of the systematic review7, the ESCHAR RCT21 reported substantially fewer recurrences after surgery at 4 years, whereas van Gent and co‐workers31 showed no difference in recurrence at 2 years. However, recently published long‐term follow‐up from the latter study showed that surgery almost halved the probability of recurrence at 10 years32, corroborating the outcome of the ESCHAR trial21. Nevertheless, these data should be interpreted cautiously.…”
Section: Discussionsupporting
confidence: 54%
“…Even if their clinical meaning is still under debate [17][18][19], their closure in patients presenting with severe venous insufficiency, such as class C5 and C6 according to the CEAP classification, significantly contributes to better results of treatment [20][21][22][23][24][25][26][27][28]. Incompetence of perforating veins can be of primary or secondary nature.…”
Section: Discussionmentioning
confidence: 99%
“…Duplex scans can be used to identify venous obstruction and valvular incompetence 48 . It is therefore useful in recognising patients who may be suitable for endovenous procedures to abolish venous reflux and to reduce the risk of VLU recurrence 49,50 .…”
Section: Box 5 | Tips On Obtaining Abpimentioning
confidence: 99%